2017
DOI: 10.4067/s0717-95022017000100054
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective Effects of Tribulus terrestris Hydro-Alcholic Extract on Non-Alcoholic Fatty Liver- Induced Rats

Abstract: ALMASI, F.; KHAZAEI, M.; CHEHREI, S. & GHANBARI, A.Hepatoprotective effects of tribulus terrestris hydro-alcholic extract on non-alcoholic fatty liver-induced rats. Int. J. Morphol., 35(1):345-350, 2017. SUMMARY:Non-alcoholic fatty liver induces many complications to the liver tissue and also serum related parameters. Medicinal plants are the safe therapeutic strategy for the treatment of diseases. In this regards, the present study was conducted to evaluate the effect of Tribulus terrestris (T. terrestris) ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 15 publications
1
10
1
Order By: Relevance
“…Previous research demonstrated that N-acetylcysteine provided protection against hepatic fibrosis in cirrhotic rat liver (13). Studies also showed that T. terrestris (4) and Ashwagandha (9) were effective in combating fibrosis in models of hepatotoxicity.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Previous research demonstrated that N-acetylcysteine provided protection against hepatic fibrosis in cirrhotic rat liver (13). Studies also showed that T. terrestris (4) and Ashwagandha (9) were effective in combating fibrosis in models of hepatotoxicity.…”
Section: Discussionmentioning
confidence: 98%
“…They administered T. terrestris at a dose of 500 mg/kg for 6 days and showed a decrease in liver enzymes. In an experimental fatty liver model induced by a high fructose diet, Almasi et al (4) reported that administered at doses of 500, 700 and 1000 mg/kg for 5 weeks led to a decrease in liver enzymes and hepatosteatosis in accordance with an increase in the dose. Their study was published after our study was completed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its various parts contain a variety of medicinally important chemical constituents, such as flavonoids, flavonol glycosides, steroidal saponins, and alkaloids. The activity depends on the concentration and the composition of active saponins, which in turn is influenced by the geographical origin of plant material [1][2][3][4][5][6]. Since the levels of Na, Mg, K, Ca, and Zn in analyzed samples of T. terrestris are higher than the levels considered as reference, the importance of the contribution by T. terrestris in the daily human needs can be considered The Ca, Fe, Zn content of the tested raw materials of T. terrestris, although high, cannot be used to supplement the intake, since any plant sources that have a high content of bi-or tri-valent ions have a low bioavailability due to their content of phytic acid, polyphenols, and tannins, which drastically limits absorption.…”
Section: Introductionmentioning
confidence: 99%
“…Its various parts contain a variety of medicinally important chemical constituents, such as flavonoids, flavonol glycosides, steroidal saponins, and alkaloids. The activity depends on the concentration and the composition of active saponins, which in turn is influenced by the geographical origin of plant material [ 1 , 2 , 3 , 4 , 5 , 6 ]. Since the levels of Na, Mg, K, Ca, and Zn in analyzed samples of T. terrestris are higher than the levels considered as reference, the importance of the contribution by T. terrestris in the daily human needs can be considered insignificant.…”
Section: Introductionmentioning
confidence: 99%